Statins Reduce Mortality After Non-severe but Not After Severe Pneumonia: A Systematic Review and Meta-Analysis - Mingwang Jia; Wenjie Huang; Li Li; Zhong Xu; Lichan Wu (Frontiers Media S.A., 2015)
PURPOSE: The objective of this study was to perform a systematic review and meta-analysis of the effects of statins on mortality for patients with non-severe pneumonia or severe pneumonia. METHODS: PubMed, EMBASE, Cochrane Database of Systematic Reviews, Cochrane central register of controlled trials and Clinicaltrials.gov were searched for the association between statins and non-severe/severe pneumonia. Eligible articles were analyzed in Stata 12.0. RESULTS: The database search yielded a total of 566 potential publications, 24 studies involving 312,309 patients met the eligibility criteria. Pooled unadjusted data showed that statin use was associated with lower mortality after non-severe pneumonia (odds ratio [OR] 0.70, 95% confidence interval [CI], 0.66-0.73), but not severe pneumonia (OR 1.05; 95% CI, 0.86-1.28). However, this protective effect of statins was weakened using adjusted estimates (OR 0.78, 95% CI, 0.75-0.82). Besides, protective effect of statins was attenuated by confounders in a subgroup analysis, especially when accounting for pneumonia severity indicators (OR 0.88; 95% CI, 0.80-0.96). CONCLUSIONS: Statin use was associated with reduced mortality after non-severe pneumonia but not severe pneumonia and this protective effect was weakened in subgroups.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.